A portable myoelectric robotic system for light exercise among bedridden and wheelchair bound individuals - Haja Mohideen, Ahmad Jazlan; Sidek, Shahrul Na'im (2010)
In this study an interactive exercise technique is developed to cater to bedridden and wheelchair bound individuals, in order for them to remain both mentally and physically alert despite their immobility. The sedentary lifestyle common among bedridden and wheelchair bound individuals leads to a variety of problems such as stiff muscles and numbness in various parts of the body. To perform this light exercise, surface electromyogram (EMG) signals are measured from major muscles from the body responsible for human motion. These measured signals are processed and further used to control the movements of a mobile robot (either left, right or straight) wirelessly using radio frequency transmission.